Daily Food Insecurity and Its Impact on Diet Quality in Low-Income Adults in Two Seasons: An Ecological Momentary Assessment Study - Rincon, Sara Jimenez (Curr Dev Nutr, 2021)
OBJECTIVES: Chronic food insecurity (FI) is common in low-income adults and is associated with a suboptimal diet. The dynamicity of FI in the short term in relation to diet is not well understood. We aim to examine if there are seasonal shifts in the relationship between FI and diet. METHODS: Low-income adults (with a household income <185% federal poverty line) were recruited in Central Pennsylvania. An ecological momentary assessment model on smartphones was used to collect daily FI and diet data over two three-week long waves: one during a fall month, and one during a winter month. An adapted USDA adult module was used to assess daily FI (“food secure” if module score = 0 or “food insecure” if module score >0). A food record was recorded on smartphones and verified by a trained dietitian via phone calls on Sunday, Monday, and Tuesday. For each subject, daily caloric intake was calculated using the Nutrition Data System for Research software. Daily Healthy Eating Index 2015 (HEI-2015) score and food group intake were calculated. Generalized estimating equation (GEE) models were used to estimate the associations between daily FI and dietary outcomes, accounting for within-person correlation and adjusting for gender, race/ethnicity, employment, and poverty status. RESULTS: 22 participants were recruited in fall 2019, 18 were followed up in winter 2020, with a total of 290 person-days (response rate = 80.64%) of data. Higher FI scores in the winter, but not in the fall, were associated with lower HEI-2015 score [b (95%CI)] [−9.06 (−14.15, −3.96)]. Higher FI in winter was associated with decreased intake of total fruit ([−0.24 (−0.44, −0.05)], whole fruit [−0.27 (−0.48, −0.06)], and whole grain [−0.52 (−1.03, −0.01)]. Higher FI in the fall months was associated with increased dairy consumption [0.65 (0.08, 1.22)]. FI was not associated with calorie intake in either season. CONCLUSIONS: This pilot study found that higher daily FI was associated with lower diet quality in the winter, but not fall, which may be driven by shifts in food accessibility and altered coping strategies across seasons. FUNDING SOURCES: The National Center for Advancing Translational Sciences, National Institutes of Health (UL1TR002014) and the Broadhurst Career Development Professorship for the Study of Health Promotion and Disease Prevention.